Oxytocin and our place in the universe - Julie R. Korenberg (Comprehensive Psychoneuroendocrinology)
Is the oxytocin-vasopressin (OT-AVP) system a part of the unseen force that subtly (in a clever and indirect way) directs our human fascination to ourselves? And is it possible that this fundamental drive is the inevitable handmaiden of the genetic selection for survival and reproduction that is played out at the level of the individual, the family and the society? Perhaps. But an equally intense biological drive to experience the unknown is intertwined and exists in the individual as “curiosity”. Both are essential for survival and success of the species. Curiously, the path to understanding ourselves, the joy of discovery and joining with others on this imperial journey to the OT-AVP system may itself be driven by the same system. I have been driven and inspired to understand “Us” for some unseen reason. This chapter relates how a driving curiosity and search for meaning led to the critical training and inspired mentorship essential for developing novel genetic, cellular and imaging technologies necessary for each advance toward this deeper understanding. Specifically, the chapter describes my recognition of human “Genetics” as the hub of medicine and the language of human neurobiology. We then set out the rationale for and sequential development of four technologies (dense whole genome arrays of genomic markers integrated with the recombination map; needed to genetically dissect and define the genetic contributions to the distinct features of brain and social behavior in Down syndrome and Williams syndrome. These include generation of 1) dense whole genome arrays of genomic markers integrated with the recombination and gene maps for defining rare cases of WS differing by one or more deleted genes, 2) analytic methods for parsing genetic contributions to standardized outcomes of cognitive and behavioral data, 3) technologies using multicolor and multi temporal fluorescence in situ hybridization to define the subcellular and neuroanatomic localization of candidate genes in the non-human primate (macaque) brain, and 4) an approach to integrating timed measures of blood neuropeptides and genomic DNA sequence variants with self-reported religious experience in devout members of the LDS church. Working across evolution and ontogeny at the cellular, neural systems and organismal levels, has led to a suspicion that a bit of the grand design may involve OT, AVP and their partners in the subtle and artful processes of the last one-half billion years that link survival of our species with our prized capacity for abstract thought and spirituality.